2009
DOI: 10.1590/s1413-85572009000100005
|View full text |Cite
|
Sign up to set email alerts
|

Leitura de histórias e evocação de estados mentais por pré-escolares

Abstract: ResumoEsta pesquisa visou investigar a evocação de termos mentais por pré-escolares de 5 e 6 anos na leitura de um livro infantil nacional contendo narrativa por imagem (Truks -Editora Ática). Os relatos individuais das crianças, selecionadas por faixa etária, foram gravados, transcritos e analisados identificando-se palavras e expressões voltadas para os estados mentais mediante 4 categorias: termos cognitivos, emocionais, de desejo/intenção e perceptivos. Os resultados indicaram que as crianças de ambas as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
0
0
1
Order By: Relevance
“…A study that analyzed the occurrence of mental states in the narrative of preschool children from pictures founds predominantly perceptive terms, focusing on physical actions of the characters more than subjective states (thoughts, emotions, desires and intentions). In this study, the authors found that is easier for children to describe observable behaviors such as the characters' actions than implicit attitudes, confirming the results of the previous study (24) .…”
Section: Discussionsupporting
confidence: 89%
“…A study that analyzed the occurrence of mental states in the narrative of preschool children from pictures founds predominantly perceptive terms, focusing on physical actions of the characters more than subjective states (thoughts, emotions, desires and intentions). In this study, the authors found that is easier for children to describe observable behaviors such as the characters' actions than implicit attitudes, confirming the results of the previous study (24) .…”
Section: Discussionsupporting
confidence: 89%
“…Essa capacidade permite aos seres humanos relacionarem-se com as outras pessoas e adaptarem-se ao meio sociocultural. (Rodrigues & Ribeiro, 2011) A criança, ao compreender que o outro pensa, sente, manifesta desejos e intenções diferentes dos dela própria e que tais desejos, intenções, pensamentos podem se alterar, apresenta maior chance de estabelecer relacionamentos sociais saudáveis (Rodrigues, Henriques & Patrício, 2009).…”
Section: Desenvolvimento Sociocognitivounclassified